Impact of Foreign Trade, Foreign Direct Investment, and Capital Expenditure on Nepal’s Economic Growth: Evidence from an Autoregressive Distributed Lag Approach - Hamal, Janga Bahadur; Sharma, Dilli Raj; Aryal, Narayan Prasad; Singh, Gobind Kumar (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study aims to analyze how exports, imports, foreign direct investment, and government capital expenditure affect Nepal’s economic growth over both shortterm and long-term periods. Design/Methodology/Approach: This research utilizes a quantitative time-series econometric methodology, specifically applying the ARDL bounds testing technique, to examine both the short-term fluctuations and long-term associations among crucial macroeconomic indicators affecting Nepal’s economic performance, based on annual data spanning from 1995 to 2023. Findings: The results reveal the existence of a long-term cointegration relationship between exports, imports, foreign direct investment, government capital expenditure, and real GDP in Nepal. Over the long run, both imports and capital expenditure are found to significantly and positively contribute to economic growth. In contrast, FDI exerts a negative influence, though statistically insignificant, while exports show a positive yet also insignificant effect on real GDP. Similar trends are observed in the short-run analysis, with capital expenditure and imports positively influencing real GDP. On the contrary, FDI has an insignificant and negative impact, and export has a positive and insignificant impact on real GDP. Conclusions: The evidence presented highlights the critical role of strategic government investment and trade policy in supporting Nepal’s economic development. The negligible impact of FDI suggests structural inefficiencies that must be addressed. Implications: These findings suggest that strategic public investment and efficient import utilization are crucial for sustained growth, while export diversification and FDIenhancing reforms are necessary to unlock their potential. Policymakers should focus on enhancing productive imports, improving FDI efficiency, and restructuring trade strategies to sustain long-term economic growth. Originality/value: Unlike previous studies based on cross-country data, this research provides a focused analysis of Nepal, employing the ARDL approach to assess the shortand long-run effects of exports, imports, FDI, and capital expenditure on economic growth. It adds value to the literature by presenting long-run evidence drawn from a single-country context. JEL Classification: F41, F43, E62, O53